Implementation of the Jakarta Smart Card Plus Policy in the South Jakarta Area - Puji Astuti, Irma Puspita; Komarudin, Komarudin; Wicaksana, Harits Hijrah; Djoko Waluyo, Surryanto (Dinasti Publisher, 2025)
In order to improve access to educational services, the Jakarta Provincial Government issued the KJP Plus policy for students from poor and vulnerable families. However, the implementation of this policy has faced challenges, particularly related to inaccurate targeting of beneficiaries, which has led to various public complaints, particularly in South Jakarta. This study aims to analyze the implementation of the KJP Plus policy in South Jakarta based on George C. Edward III's policy implementation theory, which includes aspects of communication, resources, implementer disposition, and bureaucratic structure. This study uses a descriptive qualitative approach with data collection techniques through in-depth interviews, observation, and documentation. Research informants include the Jakarta Provincial Education Office (P4OP), the South Jakarta Education Sub-Department, the Social Service Office, the Regional Development Planning Agency (BPKD), schools, and parents of beneficiary and non-beneficial students. The results of the study indicate that the implementation of the KJP Plus has run quite well administratively and socially, supported by hierarchical communication and commitment of implementers. However, limited resources, reliance on outdated administrative data, and the absence of detailed SOPs (Standard Operating Procedures) have resulted in inaccurate socioeconomic data on beneficiaries. This study recommends strengthening public communication, regularly updating recipient data, increasing implementation resources, and developing more operational standard operating procedures (SOPs). Theoretically, this research contributes to enriching studies of public policy implementation and, in practice, provides input for policy improvement.